An impact evaluation of the national prevention of mother to child HIV transmission program and MTCT associated factors in Uganda 2017–2019 - Linda Kisaakye Nabitaka; Augustina Delaney; Phoebe M. Namukanja; Fred Nalugoda; Fredrick E. Makumbi; Emilio Dirlikov; Lisa Nelson; Wilford Kirungi; Sam Sendagala; Rose B. Nakityo; Jingo Kasule; Doreen Ondo; et al. (Scientific Reports)
Abstract Uganda is consistently one of the highest burden countries for mother-to-child transmission of HIV (MTCT). This study assessed Uganda’s progress toward elimination of MTCT and factors associated with MTCT. Mother-infant pairs (MIP) were recruited at immunization clinics at randomly sampled public and private health facilities in Uganda during 2017–2019. Using a multistage sampling method, a nationally representative sample of MIP aged 4–12 weeks were recruited and followed longitudinally for 18 months or until the infant acquired HIV. Early MTCT was defined as an infant with confirmed HIV infection at study enrollment and was calculated using logistic regression to estimate adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) for associated factors. Poisson regression was used to estimate incidence rate and incidence rate ratio (IRR) for infants acquiring HIV at any time during the study after enrollment (late MTCT) and associated factors. Early MTCT was 2.2% (95% CI: 1.3–3.6) and late MTCT rate was 5.2 per 1000 person-years (95% CI: 2.5–10.9). In the adjusted model, only detectable maternal HIV viral load (≥ 1,000 copies/mL) was significantly associated with early MTCT (aOR: 6.8, 95% CI: 2.3–19.9). Similarly, ever having a detectable viral load (at any visit) was significantly associated with late MTCT (IRR: 6.2, 95% CI: 1.2–31.7). Uganda’s program has made large strides to eliminate MTCT. Identifying and addressing elevated maternal HIV viral load, especially during pregnancy and the early breastfeeding period could further reduce the number of new childhood infections in Uganda.